Mutação constitucional e a construção da tese sobre a presunção de inocência no julgamento do HC nº 126.292/SP pelo Supremo Tribunal Federal - Pastana, Luís Fernando de Souza (2017)
The purpose of this paper is to study the concept of constitutional mutation, developing its assumptions and limits, after analysing whether the Federal Supreme Court has truly implemented a legitimate informal reform of the Constitution in the judgment of HC nº 126.292/SP. The work was developed by doctrinal and jurisprudential analysis. As for the methodological approach, the research had essentially dogmatic character, in the following aspects: analytical, by the analysis of the concepts involved and the relation between them; empirical analysis, by the decision study issued by the Federal Supreme Court. The study is justified by the importance of establishing a precise concept to an informal reform of the Constitution, not regulated by law, therefore, warning that there are assumptions and, mainly, limits to be observed, under penalty of an unconstitutional mutation. The constitutional mutation was observed by its historical evolution, pointing out the authors who initially dealt with the subject. Afterwards, we analysed the means of implementation of the constitutional mutation, making a methodological cut to deepen the knowledge about the mutation implemented by a State Power. New methodological cut was made to deepen the study of the mutation developed through judicial interpretation. It was concluded that the judicial interpretation of the Constitution can lead to the occurrence of the constitutional mutation when, without altering the text of the Constitution, change the meaning of the norm, either for reasons of change in social reality, or for reasons of change in the perception of law . Two limits were pointed out to the phenomenon of constitutional mutation by means of judicial interpretation: the textual limit and the limit imposed on the derived constituent power. In the analysis of the judgment of HC nº 126.292/SP, it was observed that the change of position of the court does not have the presuppositions that characterize the constitutional mutation. In addition, it was concluded that, even if the assumptions existed, there was no respect for the textual limit and the limit imposed on the derived constituent power, for which reason the mutation was considered as an unconstitutional mutation